Analysis of Budget Execution Performance: A Case Study of Work Units within the Jurisdiction of the Bogor State Treasury Service Office - Muchamad Amrullah (Journal of Creative Power and Ambition (JCPA), 2026)
Budget execution performance indicators serve as instruments to measure the budget execution performance of work units and reflect the strengthening of "spending better" practices. This study aims to determine how to improve the budget execution performance of work units and enhance the competence of their financial management personnel. A qualitative research method using a case study approach was employed, with data collected through in-depth interviews and document reviews. Data analysis involved coding, presentation, and drawing conclusions. The findings indicate that improving budget execution performance requires: planning based on actual needs; preparing fund withdrawal plans aligned with activity schedules; executing the budget according to the plan; procuring goods and services via e-purchasing; coordinating among financial managers, procurement officials, and activity owners; monitoring and evaluating budget execution; and appointing competent financial managers and procurement officials. Competence enhancement is achieved through training, continuous self-learning, attending information sessions, communicating with relevant agencies, and engaging in discussions with fellow financial managers and procurement officials. The study recommends: penalizing work units where budget absorption is concentrated in the fourth quarter; incorporating non-technical material into training for Commitment-Making Officials (PPK); benchmarking against work units with excellent budget execution performance; developing coordination models among financial managers; and integrating the research findings into the Financial Advisor framework.